MiR-31 promotes mammary stem cell expansion and breast tumorigenesis by suppressing Wnt signaling antagonists. Issue 1 (December 2017) - Lv, Cong; Li, Fengyin; Li, Xiang; Tian, Yuhua; Zhang, Yue; Sheng, Xiaole; Song, Yongli; Meng, Qingyong; Yuan, Shukai; Luan, Liming; Andl, Thomas; Feng, Xu; et al.
Abstract MicroRNA-mediated post-transcriptional regulation plays key roles in stem cell self-renewal and tumorigenesis. However, the in vivo functions of specific microRNAs in controlling mammary stem cell (MaSC) activity and breast cancer formation remain poorly understood. Here we show thatmiR-31 is highly expressed in MaSC-enriched mammary basal cell population and in mammary tumors, and is regulated by NF-κB signaling. We demonstrate thatmiR-31 promotes mammary epithelial proliferation and MaSC expansion at the expense of differentiation in vivo. Loss ofmiR-31 compromises mammary tumor growth, reduces the number of cancer stem cells, as well as decreases tumor-initiating ability and metastasis to the lung, supporting its pro-oncogenic function.MiR-31 modulates multiple signaling pathways, including Prlr/Stat5, TGFβ and Wnt/β-catenin. Particularly, it activates Wnt/β-catenin signaling by directly targeting Wnt antagonists, includingDkk1 . Importantly, Dkk1 overexpression partially rescuesmiR31 -induced mammary defects. Together, these findings identifymiR-31 as the key regulator of MaSC activity and breast tumorigenesis. MicroRNAs play an important role in stem cell fate and tumorigenesis. In this work, the authors show thatmiR-31 controls mammary stem cell self-renewal and tumorigenesis by simultaneously activating Wnt/β-catenin and repressing TGFβ signaling pathways.